Wetlands Reform and the Criminal Enforcement Record: A Cautionary Tale - Kathleen F. Brickey (Washington University Law Quarterly, 1998)
Anecdotal narratives about environmental criminal enforcement policies and records are suspect. Their often distorted pictures of reality can lead to exaggerated claims about the existence or dimensions of problematic criminal enforcement issues. Uncritically accepted as true, those claims can provide a seemingly credible basis for misguided proposals that have the potential to do more harm than good. In the case of wetlands criminal enforcement, the anecdotal narrative would have us believe that the government is shooting wildly from the hip, with little rhyme or reason. After studying the criminal enforcement record, the best that can be said is that no matter how sincere the narrator, the narrative is utterly uninformed.
Keywords: Wetlands; Environmental crimes; Environmental law; Wetland conservation; Clean Water Act of 1977